Carbon-based conductive binding material, preparation method thereof and application of carbon-based conductive binding material in electrochemical device

By grafting polymers with bonding functional groups on the surface of the carbon-based material, the carbon-based conductive bonding material is solved, and the problems of uneven adhesive distribution in the electrode and the change in the electrode material volume are achieved, and high-energy density electrodes and electricity are achieved The preparation of the core improves the cycle life and rate performance of the battery.

CN119517984APending Publication Date: 2025-02-25BEIJING CHEHEJIA AUTOMOBILE TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311069681.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-23
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In the prior art, the binder is unevenly distributed in the electrode, resulting in delayed diffusion of electrons and lithium ions, increased polarization of the battery, and decreased cycle life and rate performance. At the same time, the volume of the electrode material changes severely during the charging and discharging process, resulting in a decrease in structural stability and capacity loss.

Method used

By grafting polymers with bonding functional groups on the surface of carbon-based material, a carbon-based conductive bonding material is constructed, functional coupling between the adhesive and the conductive agent is realized, dispersibility and conductivity inside the electrode are improved, and the electrode material is buffered. Volume variation and stress accumulation.

Benefits of technology

The preparation of high-energy density electrodes and battery cells is realized, the segregation problem of adhesives in the electrode sheet is solved, the electrode reaction kinetics and electrochemical performance of electrochemical devices is improved, the battery cycle life is extended and the magnification is improved. performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119517984A_ABST
    Figure CN119517984A_ABST
Patent Text Reader

Abstract

The invention relates to a carbon-based conductive binding material, a preparation method thereof and application of the carbon-based conductive binding material in an electrochemical device, and the carbon-based conductive binding material comprises a carbon-based material matrix and a polymer branch chain which is grafted on the surface of the matrix and has a binding functional group, and the bonding functional group is selected from any one or a combination of at least two of a fluorine group, a hydroxyl group, a carboxyl group, an ether group, a phenyl group, a cyano group or an imide group. According to the carbon-based conductive binding material provided by the invention, the dispersity of an electrode system is improved, a more stable electronic conductive network is constructed in an electrode while a binding effect is given to the electrode system, functional coupling of a binding agent and a conductive agent is realized, and the conductivity of the electrode system is improved. The energy density of the battery cell and the energy density, the rate capability and the cycling stability of the electrochemical device applying the battery cell are further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of carbon materials, and in particular to a carbon-based conductive adhesive material, a preparation method thereof, and an application thereof in an electrochemical device. Background Art

[0002] As a mature electrochemical energy storage system, lithium-ion batteries have been widely used in various fields. At present, the preparation of electrodes is mainly through mixing active materials, conductive agents and binders with solvents to form a slurry, applying it to the surface of the current collector, and drying it to obtain battery pole pieces. Although the proportion of conductive agents and binders in electrodes is low (less than 10%), high-performance binders play an important role in electrodes: binders form a complete electrode by bonding all components (active materials, conductive agents and current collectors, etc.), and form a good electron and ion percolation network by evenly dispersing active materials and conductive agents, achieving efficient carrier transmission, and alleviating the interface degradation caused by the volume change caused by the shrinkage and expansion of active materials during the charging and discharging process, so that the electrode maintains good conductivity and mechanical integrity.

[0003] However, the use of binders in electrochemical devices still has the following problems: (1) During the coating and drying process of the battery electrode, the polymer acting as a binder is likely to migrate and concentrate on the surface of the electrode active material, resulting in extremely uneven distribution of the binder in the entire electrode (Journal of Power Sources, 2017, 340, 1.), which delays the diffusion of electrons and lithium ions inside the electrode, causing the battery to be polarized, resulting in a significant reduction in cycle life and rate performance; (2) The mechanical stress accumulated in the material and the electrode during the cycle will lead to a decrease in the structural stability of the electrode, especially the electrode material based on conversion and alloying reactions, which presents a more serious volume change. Once the electrode's own bonding strength cannot adapt to the internal volume expansion, particles will break and destroy the integrity of the electrode, resulting in a sharp loss of capacity (Nature Energy, 2018, 3, 290.); (3) In order to obtain a high energy density electrode, the proportion of active material is often increased, but the corresponding reduction in the amount of conductive agent and binder will lead to poor bonding performance.

[0004] In order to solve the above problems, Mengyao Zheng et al. (Chemical Engineering Journal, 2020, 389, 124404.) designed a multifunctional composite binder by in-situ blending of waterborne polyurethane / polyacrylic acid / graphene and other materials. Among them, the strength and resilience of the material itself are enhanced by constructing a double hydrogen bond network structure inside the binder, thereby alleviating the volume change and internal resistance of the electrode during the charge and discharge process; the polyether chain in the polyurethane is used to capture ions and accelerate migration; the introduction of graphene can greatly improve the electronic conductivity of the electrode. The battery using this multifunctional composite binder has a higher discharge specific capacity, better cycle stability and superior rate performance. This design introduces a hydrogen bond network into the multifunctional composite binder, but the formation of hydrogen bonds with appropriate force inside the pole piece has special requirements for the design of functional groups inside the organic material, the use of relatively expensive graphene as a conductive carbon material, and the weak interaction between polar molecules leads to poor bonding performance. Factors such as these still restrict the design and preparation of multifunctional composite binders.

[0005] It can be seen that the uniform dispersion of active materials, conductive agents, and binder materials inside the electrode is a prerequisite for ensuring the uniform distribution of current density of ions and electrons, which is crucial for the preparation of electrodes with excellent performance. Under actual working conditions, as two additives that serve as a bridge between electrode particles and current collectors, binders and conductive agents are also crucial to the electrode reaction kinetics and the actual performance of electrochemical devices. Moreover, the most technically difficult thing is how to continue to reduce the proportion of conductive agents and binders in the electrode while taking into account the functionality of conductive agents and binders. Summary of the invention

[0006] In order to solve the above technical problems, the present disclosure provides a carbon-based conductive adhesive material, a preparation method thereof and its application in electrochemical devices. The carbon-based conductive adhesive material provided by the present disclosure integrates the binder and the conductive agent into an integrated design. On the premise of ensuring the respective performances of the binder and the conductive agent, it further reduces the proportion of the conductive agent and the binder in the electrode, increases the content of active materials, and realizes high-energy density electrodes and battery cells. At the same time, it solves the segregation problem of the binder in the electrode piece, improves the uniform dispersion of the active material, the conductive agent, and the binder material inside the electrode, ensures the uniform distribution of the current density of ions and electrons, and improves the electrode reaction kinetics and the actual performance of the electrochemical device. Moreover, the carbon-based conductive adhesive material couples the functions of the binder and the conductive agent, which can significantly buffer the internal stress accumulation of the material and the electrode piece during the cycle, maintain the dimensional stability of the particles and the electrode, and the continuous ion and electron transmission channel.

[0007] In the first aspect, the present disclosure provides a carbon-based conductive adhesive material, which includes a carbon-based material matrix and a polymer side chain having a bonding functional group grafted on the surface of the matrix, wherein the bonding functional group is selected from any one or a combination of two or more of a fluoro group, a hydroxyl group, a carboxyl group, a ether group, a phenyl group, a cyano group, an amino group, a thiol group or an imide group, and is preferably any one or a combination of two or more of a hydroxyl group, a carboxyl group, a phenyl group or an imide group.

[0008] The carbon-based conductive adhesive material provided by the present disclosure improves the dispersibility of the electrode system, and while imparting a bonding effect, constructs a more stable electronic conductive network inside the electrode, realizes functional coupling between the adhesive and the conductive agent, and further improves the energy density of the battery cell and the energy density, rate performance and cycle stability of the electrochemical device using the carbon-based conductive adhesive material. Specifically:

[0009] The carbon-based conductive adhesive material provided by the present disclosure grafts a polymer having a bonding functional group on the surface of the carbon-based material by covalent bonding, thereby constructing an integrated carbon-based conductive adhesive material. Under the premise of improving the dispersibility of the carbon material and having and maintaining the functions of the conductive agent and the adhesive, the amount of the conductive agent and the adhesive can be reduced to prepare a high energy density electrode and a battery cell. Moreover, the adhesive material is grafted on the surface of the carbon-based material, which can improve the dispersibility of each component, ensure the uniform distribution of the current density of ions and electrons, and construct a more stable carrier transfer network inside the electrode, while solving the problem of segregation of the adhesive in the pole piece, improving the energy density of the battery cell and the electrochemical performance of the electrochemical device using it. In addition, the carbon-based conductive adhesive material couples the functions of the adhesive and the conductive agent, which can significantly buffer the stress accumulation inside the material and the pole piece during the cycle process, maintain the dimensional stability of the particles and the electrode, and the continuous ion and electron transmission channel.

[0010] As a preferred technical solution of the present disclosure, the polymer having a bonding functional group is selected from any one or a combination of two or more of polyvinyl alcohol, polyacrylic acid, polyacrylonitrile, polyethylene glycol, polylactic acid, polymethyl methacrylate, methyl vinyl ether maleic anhydride copolymer, polyethylene imine, polyetherimide, polystyrene, polystyrene-butadiene rubber, polyvinylidene fluoride-hexafluoropropylene polymer, polytetrafluoroethylene, polyvinylidene fluoride, (octafluoro-N-butyl) epoxide, carboxymethyl cellulose, sodium alginate, starch, cyclodextrin, guar gum or polysaccharides.

[0011] The polymer with bonding functional groups provided by the present disclosure also has functional groups that can undergo grafting reactions with carbon-based materials so as to be grafted onto the surface of the carbon-based materials, and the bonding functional groups can provide good bonding effects.

[0012] As a preferred technical solution of the present disclosure, the surface of the carbon-based material has surface functional groups of any one of carboxyl, hydroxyl or amino, or a combination of two or more thereof.

[0013] The surface functional groups of the carbon-based material provided by the present disclosure can undergo covalent bonding reactions with polymers having bonding functional groups, so that the polymers having bonding functional groups can be grafted onto the surface of the carbon material, thereby achieving surface modification of the carbon-based material and preparation of the carbon-based conductive bonding material.

[0014] As a preferred technical solution of the present invention, based on the mass of the carbon-based material as 100%, the content of the surface functional groups is 1-20wt%, for example, 2%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, etc.

[0015] As a preferred technical solution of the present disclosure, the carbon-based material is selected from any one or a combination of two or more of zero-dimensional, one-dimensional, two-dimensional or three-dimensional carbon-based materials.

[0016] As a preferred technical solution of the present disclosure, the carbon-based material is selected from any one or a combination of two or more of porous carbon spheres, carbon nanofibers, carbon nanotubes, acetylene black, Ketjen black, natural graphite, artificial graphite, graphene, soft carbon, hard carbon or biomass-derived carbon materials.

[0017] As a preferred technical solution of the present disclosure, the mass ratio of the carbon-based material to the polymer having a bonding functional group is (1-4):1, for example, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, etc.

[0018] When the mass ratio of the carbon-based material to the polymer having a bonding functional group is within the range of the present disclosure, the obtained carbon-based conductive bonding material has a better bonding effect.

[0019] In a second aspect, the present disclosure provides a method for preparing the carbon-based conductive adhesive material described in the first aspect, the preparation method comprising: performing a grafting reaction between a carbon-based material and a polymer having a bonding functional group to obtain the carbon-based conductive adhesive material.

[0020] In the preparation method provided by the present disclosure, a polymer having a bonding functional group is grafted onto the surface of a carbon material to construct an integrated carbon-based conductive bonding material. The preparation method provided by the present disclosure has a short process, high process stability, and a wide source of raw materials with low cost. It has high economic value and development potential in the large-scale production of carbon-based conductive bonding materials and their application in electrochemical devices.

[0021] As a preferred technical solution of the present disclosure, the mass ratio of the carbon-based material to the polymer having a bonding functional group is (1-4):1, for example, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, etc.

[0022] As a preferred technical solution of the present disclosure, the temperature of the grafting reaction is 40-100°C, such as 50°C, 60°C, 70°C, 80°C, 90°C, etc., preferably 60-100°C.

[0023] As a preferred technical solution of the present disclosure, the grafting reaction time is 3-12 hours, for example, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, etc.

[0024] As a preferred technical solution of the present disclosure, the preparation method further comprises: before the grafting reaction, the carbon-based material is mixed with an oxidant for modification to obtain a carbon-based material having oxygen-containing functional groups.

[0025] The present invention utilizes an oxidant to modify a carbon-based material to obtain a carbon material having oxygen-containing functional groups on the surface, and then grafts a polymer having bonding functional groups onto the surface of the carbon material to construct an integrated carbon-based conductive bonding material.

[0026] As a preferred technical solution of the present disclosure, the mass ratio of the carbon-based material to the oxidant is 1:(20-50), for example, 1:25, 1:30, 1:35, 1:40, 1:45, etc.

[0027] As a preferred technical solution of the present disclosure, the oxidant is selected from any one or a combination of two or more of sulfuric acid, nitric acid, perchloric acid, ammonium persulfate, alkali metal persulfate, alkali metal permanganate, alkali metal dichromate, hydrogen peroxide or ozone.

[0028] The present invention utilizes an oxidant to modify a carbon-based material to obtain a carbon material having oxygen-containing functional groups on the surface, so that the carbon material can undergo a grafting reaction with a polymer having a bonding functional group.

[0029] As a preferred technical solution of the present disclosure, the reaction temperature of the modification is 40-100°C, such as 50°C, 60°C, 70°C, 80°C, 90°C, etc., preferably 40-80°C.

[0030] As a preferred technical solution of the present disclosure, the reaction time of the modification is 3-8h, for example, 4h, 5h, 6h, 7h, etc.

[0031] When the oxidant is selected from any one or a combination of two or more of sulfuric acid, nitric acid, perchloric acid, ammonium persulfate, alkali metal persulfate, alkali metal permanganate, alkali metal dichromate or hydrogen peroxide, a liquid phase oxidation method is adopted to modify the carbon-based material using the oxidant. After the reaction is completed, the carbon-based material is cooled, filtered, and washed with deionized water until the elution is neutral, and then dried to obtain a carbon-based material with oxygen-containing functional groups on the surface.

[0032] As a preferred technical solution of the present disclosure, the drying temperature is 60-100°C, such as 70°C, 80°C, 90°C, etc.

[0033] As a preferred technical solution of the present disclosure, the drying time is 10-24 hours, for example, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours, etc.

[0034] As a preferred technical solution of the present disclosure, the grafting reaction is carried out in a solvent.

[0035] As a preferred technical solution of the present disclosure, the solvent is selected from deionized water or a non-aqueous solvent.

[0036] As a preferred technical solution of the present disclosure, the non-aqueous solvent is selected from any one or a combination of two or more of N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylformamide, tetrahydrofuran, methanol, ethanol, acetone, acetonitrile, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethylene carbonate, propylene carbonate, petroleum ether, cyclohexane, carbon tetrachloride, trichloroethylene, carbon disulfide, toluene, benzene, dichloromethane, chloroform, ether, ethyl acetate or acetone.

[0037] As a preferred technical solution of the present disclosure, the mass ratio of the carbon-based material to the solvent is 1:(10-40), for example, 1:15, 1:20, 1:25, 1:30, 1:35, etc.

[0038] In a third aspect, the present disclosure provides an electrode plate, wherein the electrode plate comprises the carbon-based conductive adhesive material described in the first aspect.

[0039] The electrode plate provided by the present disclosure contains the carbon-based conductive adhesive material described in the first aspect of the present disclosure, which can effectively improve the energy density and reaction kinetics of the electrode plate, significantly buffer the stress accumulation inside the material and the plate during the cycle process, maintain the dimensional stability of particles and electrodes and continuous ion and electron transmission channels, and thus prepare an electrochemical device with excellent performance.

[0040] As a preferred technical solution of the present disclosure, the content of the carbon-based conductive adhesive material in the electrode plate is 2-24wt%, for example, 8wt%, 12wt%, 16wt%, 20wt%, etc.

[0041] In a fourth aspect, the present disclosure provides an electrochemical device, wherein the electrochemical device comprises the carbon-based conductive adhesive material described in the first aspect or the electrode plate described in the third aspect.

[0042] The electrochemical device prepared using the carbon-based conductive adhesive material provided by the present disclosure has high electrochemical reaction kinetics, high specific capacity, stable charge and discharge performance and rate performance, and can greatly improve its electrochemical performance.

[0043] Compared with the prior art, the technical solution provided by the embodiments of the present disclosure has the following advantages:

[0044] (1) The carbon-based conductive adhesive material provided by the present invention further reduces the proportion of the conductive agent and the adhesive in the electrode and increases the amount of active material on the premise of improving the dispersibility of the carbon material and ensuring the respective properties of the adhesive and the conductive agent, thereby preparing high energy density electrodes and battery cells.

[0045] (2) The carbon-based conductive adhesive material provided by the present invention can solve the problem of binder segregation in the electrode sheet, improve the uniform dispersion of active materials, conductive agents, and adhesive materials inside the electrode, ensure the uniform distribution of current density of ions and electrons, and improve the electrode reaction kinetics and the electrochemical performance of electrochemical devices.

[0046] (3) The carbon-based conductive adhesive material provided by the present disclosure couples the functions of the adhesive and the conductive agent, which can significantly buffer the stress accumulation inside the material and the electrode during the cycle process, thereby improving the structural stability and electrochemical stability of the electrode.

[0047] (4) The preparation method provided by the present disclosure has a short process flow, high process stability, and a wide source of raw materials with low cost. It has high economic value and development potential in the large-scale production of carbon-based conductive adhesive materials and their application in electrochemical devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present disclosure and, together with the description, serve to explain the principles of the present disclosure.

[0049] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0050] Figure 1 This is an infrared spectrum of the carbon-based conductive adhesive material prepared in Preparation Example 1 of the present disclosure;

[0051] Figure 2 This is a Raman spectrum of the modified conductive carbon black prepared in step (1) of Preparation Example 2 of the present disclosure;

[0052] Figure 3 The thermogravimetric curve of the modified carbon nanotube and carbon-based conductive adhesive material prepared in Preparation Example 3 of the present disclosure;

[0053] Figure 4 This is a SEM image of the carbon-based conductive adhesive material prepared in Preparation Example 4 of the present disclosure;

[0054] Figure 5 This is an EDS image of the C element in the carbon-based conductive adhesive material prepared in Preparation Example 4 of the present disclosure;

[0055] Figure 6 This is an EDS image of the O element in the carbon-based conductive adhesive material prepared in Preparation Example 4 of the present disclosure;

[0056] Figure 7 This is a SEM image of the battery electrode prepared in Example 2 of the present disclosure;

[0057] Figure 8 The electrochemical floating test diagram of the battery obtained by assembling the electrode plates of Example 4 of the present disclosure;

[0058] Fig. 9 This is a rate performance diagram of the battery assembled in Example 3 of the present disclosure. DETAILED DESCRIPTION

[0059] In order to more clearly understand the above-mentioned objectives, features and advantages of the present disclosure, the scheme of the present disclosure will be further described below. It should be noted that the embodiments of the present disclosure and the features in the embodiments can be combined with each other without conflict.

[0060] In the following description, many specific details are set forth to facilitate a full understanding of the present disclosure, but the present disclosure may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present disclosure, rather than all of the embodiments.

[0061] Preparation Example 1

[0062] This preparation example provides a carbon-based conductive adhesive material and a preparation method thereof, wherein the carbon-based conductive adhesive material includes acetylene black and a methyl vinyl ether maleic anhydride copolymer grafted on its surface, wherein the surface of the acetylene black has oxygen-containing functional groups, and the mass ratio of the acetylene black and the methyl vinyl ether maleic anhydride copolymer is 1:1.

[0063] The preparation method comprises the following steps:

[0064] (1) 0.6 g of acetylene black was dispersed in 18 g of concentrated nitric acid solution and ultrasonicated for 30 min, and stirred at a constant temperature of 60° C. for 3 h. After the reaction was complete, the mixture was cooled, filtered, and washed with deionized water until the pH value of the eluted liquid was neutral. The washed filter cake was dried at 80° C. for 12 h to obtain modified acetylene black.

[0065] (2) 0.1 g of modified acetylene black was dispersed in 3 g of N-methylpyrrolidone and ultrasonicated for 30 min and stirred for 6 h. 0.12 g of methyl vinyl ether maleic anhydride copolymer with carboxyl group was added to the above solution and stirred for 12 h at a constant temperature of 60° C. to obtain a carbon-based conductive adhesive material solution.

[0066] Preparation Example 2

[0067] This preparation example provides a carbon-based conductive adhesive material and a preparation method thereof, wherein the carbon-based conductive adhesive material includes conductive carbon black and polyacrylic acid grafted on its surface, wherein the surface of the conductive carbon black has oxygen-containing functional groups, and the mass ratio of the conductive carbon black to the polyacrylic acid is 2.5:1.

[0068] The preparation method comprises the following steps:

[0069] (1) 1 g of conductive carbon black was dispersed in a solution of 35 g of concentrated nitric acid: concentrated sulfuric acid in a volume ratio of 1:3, and ultrasonicated for 30 min, and stirred at a constant temperature of 80°C for 2 h. After the reaction was complete, it was cooled, filtered, and washed with deionized water until the pH value of the elution was neutral. The washed filter cake was dried at 60°C for 18 h to obtain the modified conductive carbon black.

[0070] (2) 1 g of modified conductive carbon black was dispersed in 35 g of dimethyl sulfoxide, ultrasonicated for 30 min and stirred for 6 h. 0.4 g of polyacrylic acid with carboxyl group was added to the above solution, stirred and reacted at a constant temperature of 80° C. for 8 h to obtain a carbon-based conductive adhesive material solution.

[0071] Preparation Example 3

[0072] This preparation example provides a carbon-based conductive adhesive material and a preparation method thereof, wherein the carbon-based conductive adhesive material includes carbon nanotubes and polyvinyl alcohol grafted on the surface thereof, wherein the surface of the carbon nanotubes has oxygen-containing functional groups, and the mass ratio of the carbon nanotubes to the polyvinyl alcohol is 3:1.

[0073] The preparation method comprises the following steps:

[0074] (1) 0.8 g of carbon nanotubes were dispersed in 36 g of hydrogen peroxide solution and ultrasonicated for 30 min, and stirred at a constant temperature of 45° C. for 7 h. After the reaction was complete, the mixture was cooled, filtered, and washed with deionized water until the pH value of the eluted liquid was neutral. The washed filter cake was dried at 100° C. for 10 h to obtain modified carbon nanotubes.

[0075] (2) 0.6 g of modified carbon nanotubes were dispersed in 15 g of N,N-dimethylformamide, and ultrasonicated for 30 min and stirred for 6 h. 0.2 g of polyvinyl alcohol with hydroxyl groups was added to the above solution, and stirred for 10 h at a constant temperature of 70°C to obtain a carbon-based conductive adhesive material solution.

[0076] Preparation Example 4

[0077] This preparation example provides a carbon-based conductive adhesive material and a preparation method thereof, wherein the carbon-based conductive adhesive material includes graphene and (octafluoro-N-butyl) epoxide grafted on its surface, wherein the graphene surface has oxygen-containing functional groups, and the mass ratio of graphene to (octafluoro-N-butyl) epoxide is 2:1.

[0078] The preparation method comprises the following steps:

[0079] (1) 1.2 g of graphene was dispersed in 48 g of potassium permanganate solution and ultrasonicated for 30 min, and stirred at a constant temperature of 70° C. for 2.5 h. After the reaction was complete, the mixture was cooled, filtered, and washed with deionized water until the pH value of the elution was neutral. The washed filter cake was dried at 70° C. for 16 h to obtain the modified graphene.

[0080] (2) 0.2 g of modified graphene was dispersed in 5.6 g of deionized water, ultrasonicated for 30 min and stirred for 6 h. 0.1 g of fluorine-containing (octafluoro-N-butyl) epoxide was added to the above solution, stirred and reacted at a constant temperature of 100° C. for 4 h to obtain a carbon-based conductive adhesive material solution.

[0081] Preparation Example 5

[0082] This preparation example provides a carbon-based conductive adhesive material and a preparation method thereof. The difference from Preparation Example 1 is that in step (1), the temperature of the reaction of acetylene black in a concentrated nitric acid solution is 100° C. and the time is 8 hours.

[0083] Preparation Example 6

[0084] This preparation example provides a carbon-based conductive adhesive material and a preparation method thereof. The difference from Preparation Example 1 is that the reaction temperature in step (2) is 40° C. and the reaction time is 4 hours.

[0085] Preparation Example 7-8

[0086] This preparation example provides a carbon-based conductive adhesive material and a preparation method thereof. The difference from Preparation Example 1 is that the mass ratios of acetylene black and methyl vinyl ether maleic anhydride copolymer in the carbon-based conductive adhesive material are 8:1 (Preparation Example 7) and 0.5:1 (Preparation Example 8), respectively.

[0087] Comparative Preparation Example 1

[0088] This comparative preparation example provides a carbon-based conductive adhesive material and a preparation method thereof, which differs from Preparation Example 1 in that step (1) is omitted, that is, acetylene black is not subjected to oxidative modification.

[0089] Comparative Preparation Example 2

[0090] This comparative preparation example provides a carbon-based conductive adhesive material and a preparation method thereof, which is different from Preparation Example 1 in that methyl vinyl ether maleic anhydride copolymer is replaced by ethylene glycol diglycidyl ether.

[0091] Comparative Preparation Example 3

[0092] This comparative preparation example provides a carbon-based conductive adhesive material and a preparation method thereof, which is different from Preparation Example 1 in that the methyl vinyl ether maleic anhydride copolymer is replaced by 1,2-epoxydodecane.

[0093] Performance Test 1

[0094] The carbon-based conductive adhesive material obtained in Preparation Example 1 was subjected to infrared testing.

[0095] Figure 1 This is the infrared spectrum of the carbon-based conductive adhesive material prepared in Preparation Example 1. As can be seen from the figure, 2880.694 cm -1 、1620.903cm -1 、1071.281cm -1 The absorption peaks at , respectively, belong to the CH vibration peak, C=O vibration peak and COC vibration peak in the methyl vinyl ether maleic anhydride copolymer. The appearance of the above peaks in the carbon-based conductive adhesive material indicates that the carbon-based material surface has a material containing the functional group (i.e., methyl vinyl ether maleic anhydride copolymer).

[0096] Performance Test 2

[0097] The modified conductive carbon black obtained in step (1) of Preparation Example 2 was subjected to Raman testing.

[0098] Figure 2 The Raman spectrum of the modified conductive carbon black prepared in step (1) of Preparation Example 2 is shown in the figure. As can be seen from the figure, the modified conductive carbon black material has a typical carbon material D peak (1341.52 cm -1 ) and G peak (1580.66cm -1). Among them, the D peak represents the defects caused by the disordered domain, and the G peak is the natural characteristic of the graphite layer. The intensity ratio of the D peak to the G peak (ID / IG) is the degree of existing defects in the carbon material. ID / IG=1.04 means that the surface of the carbon material in the modified conductive carbon black material has some defects introduced by the oxidation modification, and at the same time, the ordered graphitization degree of the carbon material itself is not excessively destroyed, and it can still play the role of electron transmission.

[0099] Performance Test 3

[0100] The carbon-based conductive adhesive material obtained in Preparation Example 3 was subjected to a thermogravimetric test.

[0101] Figure 3 The thermogravimetric curves of the modified carbon nanotubes and carbon-based conductive adhesive material prepared in Preparation Example 3. As can be seen from the figure, when the temperature rises to 300°C, the prepared carbon-based conductive adhesive material loses 25% of its mass compared with the modified carbon nanotubes, and the reduced mass comes from the polyvinyl alcohol grafted on the surface of the carbon material, which means that the carbon-based conductive adhesive material is successfully prepared.

[0102] Performance Test 4

[0103] The carbon-based conductive adhesive material obtained in Preparation Example 4 was subjected to SEM testing.

[0104] Figure 4 This is a SEM image of the carbon-based conductive adhesive material prepared in Preparation Example 4. As can be seen from the image, the carbon-based conductive adhesive material is evenly dispersed and the oxidation modification does not excessively damage the morphology and structure of the carbon-based material itself. Figure 5 This is the EDS image of the C element in the carbon-based conductive adhesive material prepared in Preparation Example 4. Figure 6 This is the EDS image of the O element in the carbon-based conductive adhesive material prepared in Preparation Example 4, indicating that there is oxygen in the carbon-based conductive adhesive material, and these oxygen elements come from the -COOH and COC groups in the binder grafted on the surface of the carbon material. Among them, the carboxylic acid group provides the carbon-based conductive adhesive material with adhesion and connection groups, while the ether group provides better dispersion performance for it by adsorbing on the surface of the carbon material.

[0105] Examples 1-11, Comparative Examples 1-3

[0106] This embodiment provides an electrode plate including a carbon-based conductive adhesive material and a method for preparing the same.

[0107] The preparation method comprises the following steps: adding the active material to the carbon-based conductive adhesive material solution obtained in Preparation Example 1-8 or Comparative Preparation Example 1-3, wherein the ratio between the active material and the carbon-based conductive adhesive material is 8:2, stirring for 6 hours to obtain a uniform viscous slurry. The viscous slurry is uniformly coated on the surface of the current collector, dried at 60° C. for 1 hour, and rolled and punched to obtain a high-stability electrode sheet.

[0108] The specific active materials and carbon-based conductive bonding material solutions used are shown in Table 1:

[0109] Table 1

[0110]

[0111]

[0112] Performance Test 5

[0113] The electrode sheet prepared in Example 2 was subjected to SEM testing.

[0114] Figure 7 This is a SEM image of the battery electrode prepared in Example 2. As can be seen from the figure, the carbon-based material is evenly dispersed around the active material, and the carbon-based material with small particle size fills the gaps between the active materials, which means that the carbon-based conductive adhesive material has good compatibility with the active material and becomes a bridge connecting the active material particles.

[0115] Performance Test 6

[0116] The electrode plate prepared in Example 4 was assembled into a battery with a lithium metal negative electrode and a commercial electrolyte.

[0117] The electrochemical stability of the battery assembled from the electrode sheets of Example 4 was measured using an electrochemical floating test at room temperature, with a voltage range of 3.0-4.9V.

[0118] Figure 8 This is an electrochemical floating test diagram of a battery obtained by assembling the electrode plates of Example 4. As can be seen from the figure, the battery is still stable at a high voltage of 4.8V, indicating that the electrode prepared using the carbon-based conductive adhesive material and the ternary nickel-manganese-cobalt material has high electrochemical stability, indicating that the modified carbon material can inhibit the aging and degradation of other materials in the battery.

[0119] Performance Test 7

[0120] The electrode sheet prepared in Example 3 was assembled into a battery with a lithium metal negative electrode and a commercial electrolyte.

[0121] The rate performance of the battery obtained in Example 3 was tested at room temperature, with a voltage range of 3.0-4.3 V and rates of 0.1C, 0.2C, 0.5C, 1C, 2C, 3C, 4C, and 5C. Fig. 9 The figure is the rate performance diagram of the battery assembled in Example 3. It can be seen from the figure that at different rates of 0.1-5C, the battery discharge capacity remains relatively stable, and still has a high discharge capacity at high rates (153.7 mAh g at 3C). -1 , 147.7mAh g at 4C -1 , 142mAh g at 5C -1 ), and the excellent rate performance proves that the introduction of carbon-based conductive binder materials can improve the multi-scale charge transfer dynamics inside the electrode.

[0122] Performance Test 8

[0123] The electrode plates prepared in Examples 1-11 and Comparative Examples 1-3 were assembled into batteries with lithium metal negative electrodes and commercial electrolytes.

[0124] The battery cycle performance was tested at room temperature, with voltage ranges of 3.0-4.2V (LFP), 3.0-4.3V (NCM, LMO), 3.0-4.4V (LCO) and 0.01-1.5V (SiOx). The positive electrode material was activated at 0.1C for three cycles and then cycled at 0.5C, and the negative electrode material was activated at 0.1A / g for three cycles and then cycled at 1A / g.

[0125] The results are shown in Table 2:

[0126] Table 2

[0127]

[0128] As can be seen from Examples 1-11, the carbon-based conductive adhesive material prepared by the present disclosure can be used in electrodes, and the prepared battery has high specific capacity and stable charge and discharge performance. When the active material is a nickel-cobalt-manganese ternary material, it exhibits a higher initial discharge specific capacity and capacity retention rate. As can be seen from Example 1, the carboxyl functional group in the methyl vinyl ether maleic anhydride copolymer can provide excellent adhesion and cohesion, and can interact with transition metal cations to inhibit their dissolution in the positive electrode, and the ether group can be adsorbed on the surface of carbon particles, so that acetylene black has a good distribution. By using the methyl vinyl ether maleic anhydride copolymer and the oxygen-containing groups on the surface of acetylene black after oxidation modification covalently bonded and the carbon-based conductive adhesive material prepared later, after matching the electrode with the active material and assembling the battery, it can present a higher electrochemical reaction dynamics, high specific capacity, stable charge and discharge performance and rate performance, and greatly improve the electrochemical performance.

[0129] From the comparison between Example 1 and Example 8, it can be seen that when the carbon-based material is over-oxidized and modified, the performance of the obtained battery decreases; from the comparison between Example 1 and Example 9, it can be seen that the carbon-based conductive adhesive material prepared at a lower reaction temperature and a shorter reaction time will cause the performance of the battery to decrease, which may be due to the lower reaction temperature and shorter reaction time causing a small amount of methyl vinyl ether maleic anhydride copolymer to be grafted onto the carbon-based material.

[0130] From the comparison between Example 1 and Examples 10-11, it can be seen that when the amount of the polymer having a binding functional group is too little (Example 10) or too much (Example 11), the performance of the obtained battery will be slightly reduced.

[0131] From the comparison between Example 1 and Comparative Example 1, it can be seen that when the carbon-based material is not oxidatively modified, the performance of the obtained battery decreases. From Comparative Examples 2 and 3, it can be seen that when the polymer with a bonding functional group provided by the present disclosure is not selected, an effective bonding effect cannot be achieved, so that the prepared carbon-based conductive bonding material cannot be effectively used in the electrode.

[0132] It should be noted that, in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0133] The above description is only a specific embodiment of the present disclosure, so that those skilled in the art can understand or implement the present disclosure. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present disclosure. Therefore, the present disclosure will not be limited to the embodiments described herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A carbon-based conductive adhesive material, characterized in that: The carbon-based conductive adhesive material includes a carbon-based material matrix and a polymer side chain having an adhesive functional group grafted on the surface of the matrix, wherein the adhesive functional group is selected from any one or a combination of two or more of a fluoro group, a hydroxyl group, a carboxyl group, a ether group, a phenyl group, a cyano group, an amino group, a thiol group or an imide group, and is preferably any one or a combination of two or more of a hydroxyl group, a carboxyl group, a phenyl group or an imide group.

2. The carbon-based conductive adhesive material according to claim 1, characterized in that: The polymer having a bonding functional group is selected from any one or a combination of two or more of polyvinyl alcohol, polyacrylic acid, polyacrylonitrile, polyethylene glycol, polylactic acid, polymethyl methacrylate, methyl vinyl ether maleic anhydride copolymer, polyethylene imine, polyetherimide, polystyrene, polystyrene-butadiene rubber, polyvinylidene fluoride-hexafluoropropylene polymer, polytetrafluoroethylene, polyvinylidene fluoride, (octafluoro-N-butyl) epoxide, carboxymethyl cellulose, sodium alginate, starch, cyclodextrin, guar gum or polysaccharide.

3. The carbon-based conductive adhesive material according to claim 1 or 2, characterized in that: The surface of the carbon-based material has a surface functional group of any one of carboxyl, hydroxyl or amino, or a combination of two or more thereof; Preferably, based on 100% of the mass of the carbon-based material, the content of the surface functional groups is 1-20 wt%.

4. The carbon-based conductive adhesive material according to any one of claims 1 to 3, characterized in that: The carbon-based material is selected from any one or a combination of two or more of zero-dimensional, one-dimensional, two-dimensional or three-dimensional carbon-based materials; Preferably, the carbon-based material is selected from any one or a combination of two or more of porous carbon spheres, carbon nanofibers, carbon nanotubes, acetylene black, Ketjen black, conductive carbon black, natural graphite, artificial graphite, graphene, soft carbon, hard carbon or biomass-derived carbon materials.

5. The carbon-based conductive adhesive material according to any one of claims 1 to 4, characterized in that: The mass ratio of the carbon-based material to the polymer having bonding functional groups is (1-4):

1.

6. The method for preparing the carbon-based conductive adhesive material according to any one of claims 1 to 5, characterized in that: The preparation method comprises: performing a grafting reaction between a carbon-based material and a polymer having a bonding functional group to obtain the carbon-based conductive bonding material; Preferably, the mass ratio of the carbon-based material to the polymer having a bonding functional group is (1-4):1; Preferably, the temperature of the grafting reaction is 40-100°C, preferably 60-100°C; Preferably, the grafting reaction time is 3-12 hours.

7. The preparation method according to claim 6, characterized in that: The preparation method further comprises: before the grafting reaction, the carbon-based material is mixed with an oxidant for modification to obtain a carbon-based material having an oxygen-containing functional group; Preferably, the mass ratio of the carbon-based material to the oxidant is 1:(20-50); Preferably, the oxidant is selected from any one or a combination of two or more of sulfuric acid, nitric acid, perchloric acid, ammonium persulfate, alkali metal persulfate, alkali metal permanganate, alkali metal dichromate, hydrogen peroxide or ozone; Preferably, the reaction temperature of the modification is 40-100°C, preferably 40-80°C; Preferably, the reaction time of the modification is 2-8h.

8. The preparation method according to claim 6 or 7, characterized in that: The grafting reaction is carried out in a solvent; Preferably, the solvent is selected from deionized water or a non-aqueous solvent; Preferably, the non-aqueous solvent is selected from any one or a combination of two or more of N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylformamide, tetrahydrofuran, methanol, ethanol, acetone, acetonitrile, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethylene carbonate, propylene carbonate, petroleum ether, cyclohexane, carbon tetrachloride, trichloroethylene, carbon disulfide, toluene, benzene, dichloromethane, chloroform, ether, ethyl acetate or acetone; Preferably, the mass ratio of the carbon-based material to the solvent is 1:(10-40).

9. An electrode plate, characterized in that: The electrode plate comprises the carbon-based conductive adhesive material according to any one of claims 1 to 5, and preferably, the content of the carbon-based conductive adhesive material in the electrode plate is 2-24 wt%.

10. An electrochemical device, characterized in that: The electrochemical device comprises the carbon-based conductive bonding material according to any one of claims 1 to 5 or the electrode plate according to claim 9.